Viral Diseases of Some Species from Penaeid Shrimp in Iraqi marine waters - Abdul Amer Reheim Jassim; Nadirah Kadhim Al-Salim (المجلة العراقية للاستزراع المائي, 2021)
A total of 140 specimens of penaeid shrimps from Metapenaeus affinis and Penaeus semisulcatus were collected from different parts of Iraqi coastal waters to detect three species of viruses Infectious Hypodermal and Hematopoietic Necrosis virus (IHHNV), White Spot Syndrome Virus (WSSV) and Monodon Baculovirus (MBV). PCR and nest PCR used to identify the viruses. The main important results in this study were detection two of more important viruses, (IHHNV) and (WSSV). So, we thought the studied shrimp was not suitable for aquaculture stock without screening because which may play a vertical and horizontal vector role. This study represents the first attempt to detect viral shrimp diseases in Iraq.